ARSITEKTUR ATAP MASJID DI KALIMANTAN SELATAN - Bambang Sakti Wiku Atmojo (BRIN, 2001)
The roofs of ancient mosques in Kalimantan based on their shape are almost all similar to each other. The similarity mainly lies in the form of multi-storey roofs known as overlapping roofs. Almost all overlapping roofs are made of shingle. The peaks are almost all in the shape of a dome, except in some mosques, such as the Wasah Hilir Mosque whose peaks are only in the form of flower arrangements. The shape of the dome is also varied, namely the shape of the onion dome, the round dome, the dome shaped like a hat, and the hexagonal dome.